Spontaneus pneumothorax in two dogs: Two clinical cases - Ocampo Salas, Luis (2020)
Two clinical cases of young dogs with signs of acute respiratory distress, without a history of trauma, are described, in which, once other pathologies were ruled out, a final diagnosis of spontaneous pneumothorax was reached.